Bidirectional Relationship Between Sleep Disturbances and Parkinson's Disease - Minakawa, Eiko N. (Frontiers in Neurology, 2022)
Parkinson's disease (PD) is the second most common neurodegenerative disease after Alzheimer's disease (AD). Both diseases share common clinical and pathological features: the gradual progression of neurological and psychiatric symptoms caused by neuronal dysfunction and neuronal cell death due to the accumulation of misfolded and neurotoxic proteins. Furthermore, both of them are multifactorial diseases in which both genetic and non-genetic factors contribute to the disease course. Non-genetic factors are of particular interest for the development of preventive and therapeutic approaches for these diseases because they are modifiable; of these, sleep is a particularly intriguing factor. Sleep disturbances are highly prevalent among both patients with AD and PD. To date, research has suggested that sleep disturbances are a consequence as well as a risk factor for the onset and progression of AD, which implies a bidirectional relationship between sleep and AD. Whether such a relationship exists in PD is less certain, albeit highly plausible given the shared pathomechanisms. This review examines the current evidence for the bidirectional relationship between sleep and PD. It includes research in both humans and animal models, followed by a discussion of the current understanding of the mechanisms underlying this relationship. Finally, potential avenues of research toward achieving disease modification to treat or prevent PD are proposed. Although further efforts are crucial for preventing the onset and slowing the progress of PD, it is evident that sleep is a valuable candidate target for future interventions to improve the outcomes of PD patients.